2019
DOI: 10.1007/s13197-019-03603-1
|View full text |Cite
|
Sign up to set email alerts
|

Influences of pulsed light-UV treatment on the storage period of dry-cured meat and shelf life prediction by ASLT method

Abstract: In order to prolong the shelf life of Chinese traditional dry-cured meat products, a pulsed ultraviolet light (PL-UV) irradiation method was adopted to treat meat products according to the following parameters: pulse energy of 8 J, 300 pulses, and an effective exposure distance of 10 cm; the UV light irradiation power of 6 W, an effective exposure distance of 11 cm, and an exposure period of 5 min. After a pulsed ultraviolet irradiation, total bacterial count in dry-cured meat decreased from 6.89 to 4.53 lg (C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 38 publications
2
11
0
Order By: Relevance
“…contamination. The results were consistent with earlier findings by Liu et al [26], who found that pulsed UV light irradiation at a distance of 11 cm, a power of 6 watts, and an exposure time of 5 minutes was sufficient to lower the Staphylococcus spp. count from 6.49 to 4.10 log cfu/gm.…”
Section: The Comparative Efficacy Of Various Dosages Of Uv-c Light (U...supporting
confidence: 93%
See 2 more Smart Citations
“…contamination. The results were consistent with earlier findings by Liu et al [26], who found that pulsed UV light irradiation at a distance of 11 cm, a power of 6 watts, and an exposure time of 5 minutes was sufficient to lower the Staphylococcus spp. count from 6.49 to 4.10 log cfu/gm.…”
Section: The Comparative Efficacy Of Various Dosages Of Uv-c Light (U...supporting
confidence: 93%
“…During the storage period, the pH decreased in both treatment groups. The current research supported earlier findings by Chun et al [39] and Liu et al [26].…”
Section: Physicochemical Parameterssupporting
confidence: 93%
See 1 more Smart Citation
“…The tissue bank has started with the processing of amnion from placenta� It hopes to expand the project to various other tissues� Strict inclusion and exclusion criteria are followed for donors and recipients� The anonymity between donor and unrelated recipient is strictly maintained� Amnion is pre-treated with glycerol to take care of the window period of HIV� It is thereafter lyophilized (freeze dried), packed, and terminally sterilized by UV-C [Figure 2]� Since lyophilization reduces the moisture by 95% and also lowers the oxygen tension, it does not support enzyme activity and, thereby prevents deterioration of the graft and thus increasing its shelf life� Further, it enables the grafts to be available on demand and facilitates their convenient storage and transport at room temperature� [1][2][3] The ultraviolet radiation (UV) technology is characterized by high efficiency, easy operation, and convenient management and has been applied in water treatment, hospital air disinfection, food packaging disinfection, and antibacterial treatment of beverages, fruits, vegetables, meat products, and sea foods� After the irradiation by short-wave ultraviolet radiation, DNAs of microorganisms break and the replication and cell division of DNA is inhibited, thus leading to cell death� Therefore, UV sterilization technology has a certain commercial value and has been applied in surface disinfection of fresh agricultural products and liquid products as well as the disinfection of air and water� [4,5] We implemented this technology to terminally sterilize the tissues� We validated the procedure in our laboratory with continuous sterility checks on the product and found it sterile for about 365 days from the date of packaging� Further studies are going on to check the shelf life of our product� Each batch of tissue samples undergo a sterility check before it is made available to the recipient as a wound dressing material� Freeze-dried amnion is used for our burns patients and is available to others at a reasonable rate that just covers the tissue processing charges�…”
Section: Setting Up a Tissue Bankmentioning
confidence: 99%
“…Cured meat is a commonly processed meat product popular among consumers for its special flavour and desirable taste worldwide. It is named differently in various countries, such as cured meat (USA), tasajo (Cuba), carne seca (Mexico), pastirma (Russia), smoked pork loin (Japan), and larou (China) (Liu et al ., 2019). Larou is a traditional Chinese dry‐cured meat with distinct flavours and long shelf‐life, produced by salting, drying, and ripening fresh livestock meat (Zhang & Zhao, 2017).…”
Section: Introductionmentioning
confidence: 99%